Efficacy of neuroendoscopic surgery and craniotomy for spontaneous supratentorial intracerebral hemorrhage - LUO Cheng⁃huan; TANG Bin; YE Ze⁃ju; QIN Jian⁃ping; LIU Xiao⁃hong (Chinese Journal of Contemporary Neurology and Neurosurgery)
Objective To investigate and compare the efficacy of neuroendoscopic surgery and craniotomy for spontaneous supratentorial intracerebral hemorrhage. Methods A total of 65 patients with spontaneous supratentorial intracerebral hemorrhage who were admitted in Dongguan People's Hospital in Guangdong, received neuroendoscopic hematoma evacuation (n = 19) or craniotomy hematoma evacuation (n = 46) from December 2019 to December 2020. The hematoma clearance rate, rebleeding rate, operation time, intraoperative blood loss, postoperative intensive care unit (ICU) length of stay, postoperative tracheotomy rate and 30 d postoperative mortality were recorded. Glasgow Coma Scale (GCS) 7 d after surgery was used to evaluated the conscious, and modified Rankin Scale (mRS) 3 months after surgery was used to assess the neurological functional prognosis. Results The hematoma clearance rate (t = 2.393, P = 0.020) and GCS score 7 d after surgery (t = 3.445, P = 0.001) in the neuroendoscopy group were higher than those in the craniotomy group, while the operation time (t = ⁃ 13.318, P = 0.000), intraoperative blood loss (t = ⁃ 7.823, P = 0.000), postoperative ICU length of stay (t = ⁃ 4.183, P = 0.000), postoperative tracheotomy rate (χ2 = 5.277, P = 0.022), and mRS score 3 months after surgery (t = ⁃ 2.493, P = 0.015) were lower than those in craniotomy group. Conclusions Neuroendoscopic surgery offers a higher hematoma clearance rate, less intraoperative blood loss, a shorter operation time and postoperative ICU length of stay, a lower postoperative tracheotomy rate, and improved postoperative conscious and neurological function prognosis, making it appropriate for clinical use.